PERAN TEKNOLOGI DALAM MEMPERKUAT DAKWAH ISLAM DI ERA DIGITAL - Hakim, Amarul (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2025)
The development of technology in the digital era has brought significant changes to various aspects of life, including the delivery of Islamic da'wah. Modern technology, especially social media, instant messaging applications, and digital content, offers great opportunities for preachers to convey religious messages more widely, quickly, and interactively. Digital da'wah not only allows for the spread of Islamic values in a creative and innovative way but also plays a role in building a moderate and harmonious understanding amidst the challenges of globalization. In addition to being a means to expand the reach of da'wah, technology is also an important tool in combating extremism and misinformation that can harm the community. By utilizing technology wisely, Islamic da'wah can develop dynamically, adaptively, and relevantly for all groups, particularly among the younger generation who have grown up with digital technology, this paper examines the strategic contribution of technological advancements to the enhancement of Islamic da’wah, the challenges faced, and the opportunities that can be maximized to create a positive impact on the community. Abstrak Perkembangan teknologi di era digital telah membawa perubahan signifikan dalam berbagai aspek kehidupan, termasuk dalam penyampaian dakwah Islam. Teknologi modern, terutama media sosial, aplikasi pesan instan, dan konten digital, menawarkan peluang besar bagi para pendakwah untuk menyampaikan pesan agama secara lebih luas, cepat, dan interaktif. Dakwah digital tidak hanya memungkinkan penyebaran nilai-nilai Islam secara kreatif dan inovatif, tetapi juga berperan dalam membangun pemahaman yang moderat dan harmonis di tengah tantangan globalisasi. Selain menjadi sarana untuk memperluas jangkauan dakwah, teknologi juga menjadi alat penting dalam melawan ekstremisme dan misinformasi yang dapat merugikan umat. Dengan memanfaatkan teknologi secara bijak, dakwah Islam dapat berkembang secara dinamis, adaptif, dan relevan bagi semua kalangan, terutama generasi muda yang akrab dengan teknologi digital. Artikel ini mengeksplorasi peran strategis teknologi dalam memperkuat dakwah Islam, tantangan yang dihadapi, serta peluang yang dapat dimaksimalkan untuk menciptakan kebermanfaatan untuk umat.